2021
DOI: 10.1101/2021.02.17.431744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequent intergenotypic recombination between the non-structural and structural genes is a major driver of epidemiological fitness in caliciviruses

Abstract: The diversity of lagoviruses (Caliciviridae) in Australia has increased considerably. By the end of 2017, five variants from three viral genotypes were present in populations of Australian rabbits, while prior to 2014 only two variants were known. To understand the interactions between these lagovirus variants we monitored their geographical distribution and relative incidence over time through a landscape-scale competition study, and from this, revealed potential drivers of epidemiological fitness. Within thr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…A previous study using this variant also reported a 100% CFR in laboratory rabbits [ 34 ], while studies reporting lower CFR used GI.3P-GI.2 variants or variants where the NS genotype was unknown [ 14 , 28 , 30 , 32 , 33 ]. The importance of recombination in generating genetic diversity in lagoviruses [ 19 , 56 ], and the fitness benefits conferred by the NS proteins [ 57 ], are only beginning to be understood, and functional analyses remain challenging without a robust cell culture system. It is critically important for future RHDV2 pathogenesis and epidemiological studies that the full variant genotype is specified.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using this variant also reported a 100% CFR in laboratory rabbits [ 34 ], while studies reporting lower CFR used GI.3P-GI.2 variants or variants where the NS genotype was unknown [ 14 , 28 , 30 , 32 , 33 ]. The importance of recombination in generating genetic diversity in lagoviruses [ 19 , 56 ], and the fitness benefits conferred by the NS proteins [ 57 ], are only beginning to be understood, and functional analyses remain challenging without a robust cell culture system. It is critically important for future RHDV2 pathogenesis and epidemiological studies that the full variant genotype is specified.…”
Section: Discussionmentioning
confidence: 99%
“…The key role of recombination in the evolution of GI.2 is well-documented [ 12 , 13 , 14 , 15 , 16 ]. Indeed, several intergenotypic and intergenogroup recombination events between pathogenic and benign strains (GI.1b, GI.3, GI.4c, GI.4e and GII.1) have been described [ 12 , 14 , 16 , 17 ], including in association with the emergence of this new genotype [ 12 ]. This places GI.2 as an orphan capsid-type lagovirus.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of recombination in generating genetic diversity in lagoviruses [19,56], and the fitness benefits conferred by the NS proteins [57], are only beginning to be understood, and functional analyses remain challenging without a robust cell culture system. It is critically important for future RHDV2 pathogenesis and epidemiological studies that the full variant genotype is specified.…”
Section: Discussionmentioning
confidence: 99%